Etiopathogenesis of Acne Vulgaris - Sema Elibüyük Aksaç; Serap Güneş Bilgili; İbrahim Halil Yavuz; Göknur Özaydın Yavuz (Van Tıp Dergisi, 2018)
Acne vulgaris is a disease of pilosebase unity which is seen generally in adolesans. Clinically lesions may appear chest, back and face and they can be mild comedonal form to cystic acne. The primary lesions of acne is comedon. Excess sebum production, abnormal follicle keratinisation, colonization of propniobacterium acnes and inflamatory mediators can play role the pathogenesis of acne. Sebaceous gland and its regulation( peroxisome proliferator activated receptors, growth hormon and insülin like growth factor regulate the sebaceous gland ) may cause the development of acne. In addition the sebaceous gland behave like a neuroendocrine-inflammatory organ which is activated corticotropin-releasing hormones in response to stress and normal functions. Pathogenic theories on acne is reviewed in this review.